PEMBERDAYAAN MASYARAKAT DAN PENINGKATAN KUALITAS KEMAMPUAN MEMBACA AL-QUR’AN ANAK-ANAK MELALUI PROGRAM MENGAJI DI MASJID AL IKHLAS DI DESA BUKIT PENINJAUAN II - Sunarti, Dwi; Saputra, Anggun; Yuniarti, Rani; Sangputri, Alena; Sri Wahyuni, Eka (CV. Kalimasada Group, 2024)
In Bukit Peninjauan II Village, we found many children reciting the Koran in the mosque, but they were not yet fluent in reciting the Koran and did not know or understand the proper and correct use of tajwid in reading the Koran. This is motivated by several underlying factors, namely the lack of teaching staff, the relatively small level of children's desire to recite the Koran, and the lack of stimulus and attention from parents. For this reason, KKN group 83 as the actor or organizer of community empowerment carries out community empowerment in improving children's Al-Qur’an reading skills in Bukit Peninjauan II Village through holding a Koran recitation program. The community empowerment steps carried out by this KKN group through the Koran recitation program consist of three stages, namely: Planning, implementation and evaluation. Meanwhile, the impact of implementing community empowerment in improving the fluency of reading the Koran through this Koran reciting program is: children reciting the Koran in Bukit Peninjauan II Village experienced quite a significant increase in reciting the Koran properly and correctly. And children are also motivated to always recite and study the Koran and memorize it in their daily lives.